Pit and Fissure Sealant: A Review - Pratyusha Mohanty (Indian Journal of Forensic Medicine & Toxicology, 2020)
In recent times, carious infection of the tooth is considered as a major worldwide concern, significantlyimpacting the health, safety and quality of life of the patients affected by it. The required routine oralhygiene procedure along with fluoride use ensures prevention against dental caries. Apart from these,another important prophylactic measure can be followed against the caries by sealing the pit and fissuresof a tooth that is more prone to caries occurrence. The main purpose of this article is to present a generaloverview of the sealing of pits and fissures, materials typically used to seal the occlusal surfaces along withthe implications and side effects. This article also presents a detailed review of safe, effective use and costeffectiveness of pit and fissure sealants as a preventive measure for caries. The finding drawn from this isthat primary, as well as permanent teeth, sealed pit and fissures are an efficient and appropriate approachfor preventing and arresting dental caries. But conducting a proper regular dental check-up is necessary toensure that there is no advanced tooth decay caused due to any leakage in the sealing.